Digital Media & Intellectual Property Management of Rights and Consumer Protection in a Comparative Analysis - Lucchi, Nicola (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This book focuses on intellectual property issues and rights in digital - dia, their connection with consumer protection, and the limits on freedom of contracts imposed by technological power. In particular, it analyzes, from a EU and U.S. comparative perspective, the complex issues concerning legal protection, technological measures and new business models associated with the use, distribution, and control of digital media. The book is based on a research project the author started in 2001 as V- iting Scholar at the University of California at Berkeley, Boalt Hall School of Law, later developed as Visiting Scholar at the University of Texas at Austin, School of Law and concluded as Research Associate at the Dip- timento di Scienze Giuridiche - Sezione di Rovigo of the University of Ferrara and as non residential Fellow of the Center for Internet and So- ety, Stanford Law School. Research support for this book has been provided by Fondazione Cassa di Risparmio di Padova e Rovigo, Rotary Foundation Ambassadorial Scholarship and University of Ferrara. I am particularly indebted to Robert Cooter, Mark Lemley and Pamela Samuelson for providing the occasion that inspired this work while I was at the University of California at Berkeley. I wish to thank all my colleagues and friends from the University of Ferrara, who offered me support, advice and encouragement when I most needed it.